FIRST DATA ON MICROELEMENTAL COMPOSITION OF BENTHIC ORGANISMS FROM THE 9°50′ N HYDROTHERMAL FIELD, EAST PACIFIC RISE - Demina L.L.; Galkin S.V.; Lein A.Yu.; Lisitsyn A.P. (My University, 2007)
Hydrothermal vents on the ocean bottom are surrounded by geochemical barriers related to extreme gradients of water temperature and concentrations of reduced compounds and heavy metals. Such conditions promote the formation of unique bottom communities characterized by symbiothrophy, i.e., utilization of nutrients produced by bacterial symbionts in the process of chemosynthesis. It is evident that hydrothermal communities with a biomass of ~10 kg/m2, which is anomalous for the pelagic zone, can participate in biodifferentiation, i.e., change the fate of the chemical elements delivered from hydrothermal vents. However, the available publications, in which only some tissues of particular organisms rather than the bottom community as a whole have been investigated, are insufficient to estimate the geochemical implications of the benthos.